2022
DOI: 10.3390/ijms231911276
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Antimicrobial Resistance in Clinically Relevant Bacteria Isolated at the Human/Animal/Environment Interface Using Whole-Genome Sequencing in Austria

Abstract: Antimicrobial resistance (AMR) is a public health issue attributed to the misuse of antibiotics in human and veterinary medicine. Since AMR surveillance requires a One Health approach, we sampled nine interconnected compartments at a hydrological open-air lab (HOAL) in Austria to obtain six bacterial species included in the WHO priority list of antibiotic-resistant bacteria (ARB). Whole genome sequencing-based typing included core genome multilocus sequence typing (cgMLST). Genetic and phenotypic characterizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 83 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…But, in this study, a strong correlation was shown that some beta lactam and uroquinoloe antibiotics resistance were co-existed; there were also evidences for the co-existence of uroquinolone, beta lactam group ARGs with beta lactams, uroquinolones and aminoglycoside antibiotic groups 39,40 . Previous study demonstrated that genotypic factors play a signi cant role in in uencing phenotypic antibiotic resistance 41 .…”
Section: Discussionmentioning
confidence: 99%
“…But, in this study, a strong correlation was shown that some beta lactam and uroquinoloe antibiotics resistance were co-existed; there were also evidences for the co-existence of uroquinolone, beta lactam group ARGs with beta lactams, uroquinolones and aminoglycoside antibiotic groups 39,40 . Previous study demonstrated that genotypic factors play a signi cant role in in uencing phenotypic antibiotic resistance 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria are indeed continuously exchanging genetic determinants, thus contributing to the public health concern towards antibiotic resistance dissemination [8]. E. coli is the best example of bacterial species that may promote the transfer of resistance genes to humans [55], to food-producing [9][10][11] and companion animals [56], and within the environment [12]. Although antibiotics present in sub-inhibitory concentrations may contribute to the development of antibiotic resistant strains, they have also been shown to participate in the dissemination of the corresponding resistance genes.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is an increasing number of reports associating heavy metals [3,4] and other compounds such as detergents [5], nanomaterials [6], and pesticides [7] as promoters for the dissemination of antibiotic resistance. Such spread is mainly linked to plasmids carrying resistance genes in Gram negatives among isolates identified in humans [8], in the food chain [9][10][11], or in the environment [12].…”
Section: Introductionmentioning
confidence: 99%
“…It is now well admitted that the problem of antimicrobial resistance, particularly associated with E. coli species, is not limited to human clinical isolates and that extra sources such as food products, 22 , 30 , 31 companion animals 32 and the environment 33 also represent a major source of concern. Our study was designed to evaluate the possible impact that antibiotics used in veterinary practice may have on the transfer of plasmids encoding the main antibiotic resistance determinants identified in animals and that might possibly be further transferred to human pathogens.…”
Section: Discussionmentioning
confidence: 99%